Reading and Teaching: A Book About Learning - Catherine F. Compton-Lilly (Networks: An Online Journal for Teacher Research, 2007)
The series editors, Daniel Liston and Ken Zeichner, tell us that the book Reading and Teaching is designed to help teachers engage with “crucial issues that all teachers need to address.” I believe they are right. This book does not offer simple solutions, bulleted lists of recommendations, or formulas for becoming a star teacher. This book makes you think good and hard about being a literacy educator and lays bare the complexities of teaching literacy well.